2022
DOI: 10.7759/cureus.32540
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Harmless Acute Pancreatitis Score (HAPS) and Bedside Index of Severity in Acute Pancreatitis (BISAP) Scoring System in the Stratification of Prognosis in Acute Pancreatitis

Abstract: Acute pancreatitis is a common disease in patients presenting to the emergency room in any hospital. The most common causes are alcohol ingestion and gallstone disease. Diagnosis is usually based on clinical findings and elevated serum amylase and lipase levels. Imaging is often not necessary but may be used to confirm the diagnosis or rule out any other pathology or to evaluate for any complications. The majority of patients will have a mild, self-limiting disease but others may develop a severe fulminant cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…HAPS may offer significant advantages in the triage of AP patients when compared to other scoring systems, underscoring its potential utility in optimizing patient classification and guiding treatment strategies. In a study including 60 patients with the first attack of AP, Gupta et al [ 145 ] reported that the sensitivity, specificity, PPV, NPV, and AUC of HAPS predicting SAP were 90.91%, 59.81%, 33.33%, 96.67%, and 0.75, respectively. The high NPV indicated that HAPS could very accurately identify within the first hour of admission patients who had a mild course of disease, did not require intensive management, and were not at risk of dying from the disease[ 145 ].…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…HAPS may offer significant advantages in the triage of AP patients when compared to other scoring systems, underscoring its potential utility in optimizing patient classification and guiding treatment strategies. In a study including 60 patients with the first attack of AP, Gupta et al [ 145 ] reported that the sensitivity, specificity, PPV, NPV, and AUC of HAPS predicting SAP were 90.91%, 59.81%, 33.33%, 96.67%, and 0.75, respectively. The high NPV indicated that HAPS could very accurately identify within the first hour of admission patients who had a mild course of disease, did not require intensive management, and were not at risk of dying from the disease[ 145 ].…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
“…In a study including 60 patients with the first attack of AP, Gupta et al [ 145 ] reported that the sensitivity, specificity, PPV, NPV, and AUC of HAPS predicting SAP were 90.91%, 59.81%, 33.33%, 96.67%, and 0.75, respectively. The high NPV indicated that HAPS could very accurately identify within the first hour of admission patients who had a mild course of disease, did not require intensive management, and were not at risk of dying from the disease[ 145 ]. Based on this result, they argued that the patient typically tended to experience a milder course of illness if the evaluation of HAPS yielded a negative result[ 145 ].…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] There is no specific treatment for AP, and the treatment is supportive. [11] The treatment approach is mainly based on fluid administration, enteral nutrition, and pain management. [12] Scoring systems and biochemical markers that predict disease severity are widely used in AP management.…”
Section: Introductionmentioning
confidence: 99%